Deposição de nutrientes em rã-touro na fase de engorda - Pereira, Marcelo Maia [UNESP]; Mansano, Cleber Fernando Menegasso [UNESP]; Peruzzi, Nelson José [UNESP]; De Stéfani, Marta Verardino [UNESP] (My University, 2015)
Descriptions of nutrient deposition are important to determine the nutritional requirements of animals. The objective of this study was to describe nutrient deposition in the body and legs and the dietary intake of protein and fat of bullfrogs during the fattening phase using Gompertz and logistic models, and to evaluate feed efficiency. A total of 2,375 froglets with an initial weight of 7.03 ± 0.16 g were housed in five fattening pens. The animals were fed a commercial diet containing 40% crude protein. Frogs and their legs were weighed and sampled at intervals of 14 days for the determination of nutrient composition. On the basis of the model selection criteria, the logistic model was the most adequate to describe nutrient deposition in the body and legs of bullfrogs and the dietary intake of protein and fat. With respect to nutrient deposition in the body, the estimated values for nutrient weight at maturity (Wm) and the time when the maximum rate of deposition was attained (t*) were 244.3 g and 106 days, 55.2 g and 113 days, 30.9 g and 124 days, and 8.6 g and 99 days for water, protein, fat and ashes, respectively. For nutrient deposition in the legs, these values were 77.6 g and 111 days, 14.5 g and 104 days, 1.4 g and 86 days, and 3.7 g and 119 days, respectively. The protein efficiency of the bullfrog diet was low (36.76%), whereas the efficiency of fat utilization was high (140.9%), indicating the need to develop an ideal diet for bullfrogs.
Nutrient deposition in bullfrogs during the fattening phase
Keywords: Fat deposition; Lithobates catesbeianus; Logistic; Protein deposition